Solidification microstructure and phase transition of La-Nd-Fe alloys. (14th October 2020) - Su, D; Yang, K C; Rong, M H; Cheng, X; Wei, Q; Yao, Q R; Wang, J; Rao, G H; Zhou, H Y
Abstract: The solidification microstructure and phase transition of ten La-Nd-Fe alloys were studied experimentally by scanning electron microscopy (SEM) with energy dispersive x-ray spectroscopy (EDS) and differential thermal analysis (DTA). Phase compositions and phase transition temperatures of La-Nd-Fe alloys were measured and the formed phases were identified. The solidification behavior of La-Nd-Fe alloys was analyzed based on the experimental results of both solidification microstructure and phase transitions with the reported Nd-Fe, La-Fe and La-Nd sub-binary phase diagrams. The results indicated that the solidification processes of all La-Nd-Fe alloys begin with the precipitation of primary phase fcc( γ -Fe) and then follow by the formation of bcc( α -Fe) and/or Fe17 Nd2 phases through different peritectic reactions. The solidification microstructure of three Fe65 La29 Nd6, Fe65 La25 Nd10 and Fe65 La22 Nd13 alloys presents three-phase microstructure with bcc( α -Fe), Fe17 Nd2 and fcc(La, Nd) phases, while that of three Fe65 La19 Nd16, Fe65 La9 Nd26 and Fe65 La15.5 Nd19.5 alloys shows three-phase microstructure with bcc( α -Fe), Fe17 Nd2 and dhcp(La, Nd) phases. The two-phase micorstructure with Fe17 Nd2 and dhcp(La, Nd) ohases was formed in the solidification microstructure of four Fe65 La12 Nd23, Fe65 La6.5 Nd28.5, Fe65 La4 Nd31 and Fe65 La1.5 Nd33.5 alloys. Moreover, no stable ternary intermetallic compound was found in the present experiments. The solidification microstructure and phase transition of La-Nd-Fe alloys would provide a basis for the design of La-Nd-Fe-B magnetic alloys.